MODEL OF IMROVING WORK LOAD AND FAMILY WORK CONFLICT BASED HR PERFORMANCE ON REGIONAL FINANCIAL AGENCY OF SEMARANG REGENCY - Teguh Adi Sunanto; Budhi Cahyono (UNISSULA, 2017)
This research is intended to test the effect of workload and family work conflict on HR performance with social capital as moderation. The problem is how to improve HR performance through the reduction of workload, family work conflict and work stress with social capital as moderation. The sample of this study is employees of Regional financial agency of Semarang as many as 117 respondents. Regression Analysis was done by software package for statistical social science (spss). The analysis showed that the workloads and family work conflict have significant effect on HR performance with social capital as moderation. The empirical findings indicated that workload has significant effect on HR performance; family work conflict has a significant effect on HR performance; workload has significant effect on work stress; family work conflict has significant effect on work stress; social capital moderates workload to affect HR performance; and social capital moderates the effect of family work conflict to affect HR performance.Keywords : workload, family work conflict, work stress, social capital and HR performance.